Peran Mental Toughness terhadap Stres Akademik pada Mahasiswa yang Mengikuti Organisasi - Mirizon, Muhammad Abror; Nugroho, Indra Prapto; Iswari, Rosada Dwi (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2024)
This study aims to find out whether there is a role of mental toughness in academic stress in Sriwijaya University students who join organizations. The hypothesis in this research is that there is a role of mental toughness in academic stress in Sriwijaya University students who join organizations. Participants in this research were 229 active Sriwijaya University students who were still active members of the organization. The sampling technique used was purposive sampling. The mental toughness variable was measured using a psychological scale compiled by researchers referring to the components of Clough & Strycharczyk (2011). Meanwhile, to measure the academic stress variable, the psychological scale is prepared based on aspects from Bedewy & Gabriel (2015). The result of cronbach's alpha reliability shows 0.875 for the academic stress scale, and 0.914 for the mental toughness scale. The results of the simple regression analysis show that mental toughness and academic stress have a significance value of 0.000 (p<0.05) with a value of R = 0.754. Analysis of this data indicates the role of mental toughness in academic stress. Thus, the hypothesis proposed in this research can be accepted. The results of the test on the effective contribution of mental toughness show a contribution of 57.1% to academic stress of Sriwijaya University students who join the organization.